2018
DOI: 10.1111/odi.12825
|View full text |Cite
|
Sign up to set email alerts
|

Sjögren's syndrome X‐chromosome dose effect: An epigenetic perspective

Abstract: Sjögren's syndrome (SS) is a chronic autoimmune disease affecting exocrine glands leading to mouth and eyes dryness. The extent to which epigenetic DNA methylation changes are responsible for an X-chromosome dose effect has yet to be determined. Our objectives were to (i) describe how epigenetic DNA methylation changes could explain an X-chromosome dose effect in SS for women with normal 46,XX genotype and (ii) determine the relevant relationships to this dose effect, between X-linked genes, genes controlling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 79 publications
0
21
0
Order By: Relevance
“…Along these lines, recent studies in humans found increased frequency of an extra X chromosome in males and females with Sjögren syndrome supporting the role of X chromosome genes in increasing risk of autoimmunity. Similarly, epigenetic DNA methylation changes may contribute to an increased dose effect by allowing access to genes on the inactivated X chromosome in females with normal karyotypes …”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, recent studies in humans found increased frequency of an extra X chromosome in males and females with Sjögren syndrome supporting the role of X chromosome genes in increasing risk of autoimmunity. Similarly, epigenetic DNA methylation changes may contribute to an increased dose effect by allowing access to genes on the inactivated X chromosome in females with normal karyotypes …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we propose that NEAT1-miR-212-3p/miR-132-3p/miR-129-5p-TTK might be a potential RNA regulatory pathway to regulate the disease progression of early RA. Additionally, although lncRNA XIST has not been reported in RA, it has been reported to be upregulated in another autoimmune disease, Sjogren's syndrome [31]. We hypothesize that XIST-miR-25-3p/miR-129-5p-GZMA has an important regulatory role in RA.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, expression of MMP9 promotes lymphocytic infiltration in the SG tissue (Perez et al, ). Meanwhile, increased MMP9 expression in SGECs is a pathogenic hallmark of pSS, resulting as a consequence of the action of etiological factors, for example, X chromosome dose effect and interactions with lymphocytes impairing the PKC‐gamma/ERK/DNMT1 pathway in SGECs (Mougeot, Noll, & Bahrani Mougeot, ; Renaudineau & Ballestar, ).…”
Section: Discussionmentioning
confidence: 99%